Thyroid Hormone Receptor Alpha Mutations Lead to Epithelial Defects in the Adult Intestine in a Mouse Model of Resistance to Thyroid Hormone - Bao, Lingyu (Thyroid, 2019)
Background: The thyroid hormone triiodothyronine (T3) is critical for vertebrate development and affects the function of many adult tissues and organs. Its genomic effects are mediated by thyroid hormone nuclear receptors (TRs) present in all vertebrates. The discovery of patients with resistance to thyroid hormone (RTHβ) >50 years ago and subsequent identification of genetic mutations in only the THRB gene in these patients suggest that mutations in the THRA gene may have different pathological manifestations in humans. Indeed, the recent discovery of a number of human patients carrying heterozygous mutations in the THRA gene (RTHα) revealed a distinct phenotype that was not observed in RTH patients with THRB gene mutations (RTHβ). That is, RTHα patients have constipation, implicating intestinal defects caused by THRA gene mutations. Methods: To determine how TRα1 mutations affect the intestine, this study analyzed a mutant mouse expressing a strong dominantly negative TRα1 mutant (denoted TRα1PV; Thra1(PV) mice). This mutant mouse faithfully reproduces RTHα phenotypes observed in patients. Results: In adult Thra1(PV/+) mice, constipation was observed just like in patients with TRα mutations. Importantly, significant intestinal defects were discovered, including shorter villi and increased differentiated cells in the crypt, accompanied by reduced stem-cell proliferation in the intestine. Conclusions: The findings suggest that further analysis of this mouse model should help to reveal the molecular and physiological defects in the intestine caused by TRα mutations and to determine the underlying mechanisms.